Replacement of Artemia with Moina micrura in the rearing of freshwater shrimp larvae - Alam, M.J.; Ang, K.J.; Begum, M. (Kluwer Academic Publishers, 1995)
The effect of an abrupt change in the live diet of shrimp larvae was investigated by replacing Artemia with Moina micrura. The control treatment consisted of feeding Artemia throughout the rearing period (regime A), while in the other treatments the onset of Moina feeding was arbitrarily chosen at larval stages iv (A3M), vi (A5M), viii (A7M) and x (A9M). No significant differences (α = 0.05) were observed among the treatments during larval production, mean stage development (MSD) and growth of postlarvae. The mean (SD) yields of postlarvae (PL) were 11.97 (1.98), 15.10 (2.92), 14.72(1.56), 13.51 (1.74) and 12.70 (1.40) PL l-1 respectively for the feeding regimes A3M, A5M, A7M, A9M and A. Up to stage v, the ingestion rate in the Moina treatment was as low as 0.01-0.47 larva-1 h-1 compared with that in the Artemia treatment (0.29-1.77 larva-1 h-1). However, the ingestion of Moina increased from stage vi-vii onwards. © 1995 Chapman & Hall.